2019
DOI: 10.1057/s41599-019-0352-4
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinarity revisited: evidence for research impact and dynamism

Abstract: Addressing many of the world's contemporary challenges requires a multifaceted and integrated approach, and interdisciplinary research (IDR) has become increasingly central to both academic interest and government science policies. Although higher interdisciplinarity is then often assumed to be associated with higher research impact, there has been little solid scientific evidence supporting this assumption. Here, we provide verifiable evidence that interdisciplinarity is statistically significantly and positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 33 publications
0
82
0
5
Order By: Relevance
“…Of the assumptions that underpin the research presented here, perhaps the most fragile is the one that policy interventions can foster increased interdisciplinarity in the research groups they target. For instance, many studies documented trends towards increased interdisciplinarity in research, but without specifically linking this shift to policy interventions (Dworkin, Shinohara, & Bassett, 2019;Okamura, 2019;Porter & Rafols, 2009); or, as we just did above, they note the multiplication of interdisciplinarity initiatives and narratives originating from policymakers. If proved effective, these initiatives could be very important in fostering cross-disciplinary research as there is quantitative evidence demonstrating that traditional grant mechanisms tend to be conservative and to shy away from cross-disciplinarity.…”
Section: Fostering Of Interdisciplinary Research Practices Through Funding Instruments and Other Policy Interventionsmentioning
confidence: 94%
“…Of the assumptions that underpin the research presented here, perhaps the most fragile is the one that policy interventions can foster increased interdisciplinarity in the research groups they target. For instance, many studies documented trends towards increased interdisciplinarity in research, but without specifically linking this shift to policy interventions (Dworkin, Shinohara, & Bassett, 2019;Okamura, 2019;Porter & Rafols, 2009); or, as we just did above, they note the multiplication of interdisciplinarity initiatives and narratives originating from policymakers. If proved effective, these initiatives could be very important in fostering cross-disciplinary research as there is quantitative evidence demonstrating that traditional grant mechanisms tend to be conservative and to shy away from cross-disciplinarity.…”
Section: Fostering Of Interdisciplinary Research Practices Through Funding Instruments and Other Policy Interventionsmentioning
confidence: 94%
“…In the field of science, this often leads to the fact that women tend to publish in new and emerging fields of science, not yet dominated by male colleagues. Those new fields are often interdisciplinary in nature and typically associated with higher shares of citations (Okamura 2019, Wang et al 2015. From a business perspective, the presence of diversity balances biases, which thereby contributes to the generation of alternative perspectives and experiences for exploring new problems.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, we observed that commensality should have a role in health promotion as an interesting concept and object of research in nutrition [ 8 , 9 ]. Interdisciplinarity should play an essential role [ 28 ], and cultural and nutritional aspects are fundamental parts of this comprehensive Mediterranean model or lifestyle [ 29 ]. This statement is not new and corresponds to an old claim on the part of food anthropologists [ 30 ] 3/5/2021 4:37:00 PMand other social scientists.…”
Section: Conclusion: Commensality As a Cultural Driver Related Tomentioning
confidence: 99%